Respon Pemberian Fermentasi Air Kelapa (Cocos nucifera L.) Terhadap Pertumbuhan Tanaman Selada Keriting (Lactuca sativa L. var. Grand rapids F1) - Windi Royani; Sulistyo Sidik Purnomo; Hayatul Rahmi (Peneliti.net, 2021)
The experiments were implemented in Lebaksari, Wadas Village, East Telukjambe Subdistrict, Karawang County from April to June 2021. The study was compiled using experimental methods with a single factor Random Group (RAK) design. The factor tested was the use of a solution of coconut water fermentation (P) yield with 5 degrees, treatment repeated 5 times. The tariff used is P0 (without treatment), P1 (25% coconut water fermentation), P2 (50% coconut water fermentation), P3 (75% coconut water fermentation), and P4 (100% coconut water fermentation). There is a real influence from the result of giving a coconut water fermentation to the high observation parameters of 7 hst and 28 hst age plants. P2 treatment (50% coconut water fermentation) shows the best result at 7 hst age plant height of 11.40 cm and the best result at 28 hst age plant height contained on treatment P1 (25% coconut water fermentation) of 31.67 cm.